Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.3308
|View full text |Cite
|
Sign up to set email alerts
|

THU0138 Das 28 correlated poorly with the objective evidence of inflammation as detected by ultrasound (US) examination of hands and feet in patients with established rheumatoid arthritis (RA)

Abstract: BackgroundThe Disease Activity Score including 28 joint count (DAS-28) is the most widely used outcome measure in RA. However, despite evidence that metatarsophalangeal (MTP) joints are often the first joints affected in RA, DAS-28 score does not incorporate them.ObjectivesOur study aimed to investigate the correlation between DAS-28 assessment and objective evidence of active joint inflammation using the US examination of both hands and feet, including wrists, metacarpophalangeal (MCP), proximal interphalange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…At Week 24, for combined treatment groups, PDUS change did not significantly correlate with clinical activity change (Week 24 minus baseline) by any measure (p>0.05) consistent with previous reports 5 6. In contrast, at Week 24, GSUS change correlated with changes in all clinical activity scores evaluated (r=0.40–0.59) except DAS28-CRP.…”
supporting
confidence: 85%
“…At Week 24, for combined treatment groups, PDUS change did not significantly correlate with clinical activity change (Week 24 minus baseline) by any measure (p>0.05) consistent with previous reports 5 6. In contrast, at Week 24, GSUS change correlated with changes in all clinical activity scores evaluated (r=0.40–0.59) except DAS28-CRP.…”
supporting
confidence: 85%
“… 38–45 In a study in established patients with RA in whom there was explicit doubt about the presence of inflammation, only weak and non-statistically significant correlations between US sum scores and composite indices were found. 46 This suggests that US may be better related to ‘true’ inflammatory activity in these patients and may have additional value in patients with D2T RA in whom a doubt about the presence of inflammatory activity exists. However, the minimal number of joints that should be included in an US assessment remains unclear, 41 which hampers the use of a sum score to determine the overall level of disease activity in daily practice.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45] In a study in established patients with RA in whom there was explicit doubt about the presence of inflammation, only weak and non-statistically significant correlations between US sum scores and composite indices were found. 46 on August 29, 2021 by guest. Protected by copyright.…”
Section: Points To Considermentioning
confidence: 99%
“…Only one study (moderate RoB) explicitly evaluated patients in whom there was doubt about the presence of inflammation, although this study did not report appropriate diagnostic association measures. 25 In patients who had symptoms suggestive of inflammatory joint pain, weak or non-statistically significant correlations were found between DAS28 and US sum scores (US sum scores of hands and feet: r=0.14; US sum scores of MTP joints: r=0.03). In established patients with RA in whom there was not explicit doubt about the presence of inflammation, moderate to strong correlations between US sum scores and composite indices were found in eight other papers (range of r: 0.40–0.70, statistically significant (s) in six of eight papers (two low RoB, five moderate RoB, one high RoB)).…”
Section: Resultsmentioning
confidence: 95%
“…In this study, only weak and statistically non-significant correlations were reported between an US sum score and DAS28. 25 In the general population of RA patients who are not treatment naïve, US was studied most extensively among all diagnostic tests in papers with low to moderate RoB. 24 27 35 40 67 74 78 83 All papers reported moderate to strong correlations between DAS28 and US sum scores, although also here appropriate diagnostic association measures were not reported.…”
Section: Discussionmentioning
confidence: 99%